THE CORRELATION BETWEEN THE USE OF LANGUAGE LEARNING STRATAGIES (LLSs) AND LISTENING ACHIEVEMENT - M. Rofiq (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
ABSTRACT Listening is a fundamental element in language skill. Unfortunately, many students still confront some cases and problems. The problems frequently come from several factors, and a factor that significantly influence, is the strategy. The strategy listening has some aspects of Cognitive, Metacognitive, and socio-affective. Those aspects become high determination whether students are succeess in their listening achievement. Therefore, the researcher has high curiosity to conduct the research with 3 goals; to find out the strategies that frequently used by the students, to investigate whether there is significant difference in the use Language Learning Strategies (LLSs) in learning listening skill by successful and less successful learners, to identify the correlation between strategic learning and listening achievement.This study applied quantitave approach as the research design. The population took from 97 students who are second semester at UNISMA that consisted 4 classess (A,B,C,D). In  collecting the data, the researcher used 2 intruments; SSLQ questionnaire to attain strategic learning data and documentation to gain listening achievement data. while the techniques are giving  the questionnaire to students and collecting the listening score from lecturer’s document. In order to analyze the data, the researcher measured through IBM SPSS  version  25.The result of study showed that between two variables learning strategies and listening achievement are not correlated due to Sig.(2-tailed) 0.771 bigger than level of significant > (0,05). In terms of succesful and less successful learners, they have Sig. (2-tailed) 0.000 smaller that level of significant < (0.05), then it proved between two variables have significant difference. Moreover, among 3 aspects of learning strategies, English students at Unisma  have higher tendency in using socio-affective rather than cognitive and metacognitive.KEY WORDS: Learning Strategies, Listening Achivement, Successful and Less Successful learners